1997
DOI: 10.1046/j.1365-2109.1997.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Stocking density effects on larval growth and survival of two catarina scallop, Argopecten ventricosus(= circularis) (Sowerby II, 1842), populations

Abstract: Two populations of catarina scallop, Argopecten ventricosus (= circularis) (Sowerby II, 1842), were evaluated for their larval growth and survival responses to different stocking densities. Larvae from the Magdalena population had a significantly higher growth but equal survival at a density of 10 larvae ml−1 compared with 20 larvae ml−1. Larvae from the Concepcion population grew better at densities of 15 and 20 larvae ml−1 than at densities of 5 and 10 larvae ml−1, although survival was lower at higher densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…Likewise, a low larval density of 1-2 ml )1 was employed for hatchery reared Placopecten magellanicus, while A. irradians were reared at 5-10 ml )1 (Couturier et al 1995). The average initial and final larval densities in our study were well below critical densities (<10 ml )1 ) reported for scallops (MacDonald 1988;Robert et al 1996;Ibarra et al 1997). These results are in conformity with the recommended rearing density of 8-10 larvae ml )1 of P. maximus in the UK (Millican 1997).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, a low larval density of 1-2 ml )1 was employed for hatchery reared Placopecten magellanicus, while A. irradians were reared at 5-10 ml )1 (Couturier et al 1995). The average initial and final larval densities in our study were well below critical densities (<10 ml )1 ) reported for scallops (MacDonald 1988;Robert et al 1996;Ibarra et al 1997). These results are in conformity with the recommended rearing density of 8-10 larvae ml )1 of P. maximus in the UK (Millican 1997).…”
Section: Discussionsupporting
confidence: 91%
“…Initial larval densities on day 3 were within the range (1-30 larvae ml )1 ) reported from other bivalve studies (MacDonald 1988;Ibarra et al 1997 andreferences therein, Uriarte et al 2001b;Torkildsen and Magnesen 2004). It has been shown that a stocking density of 20 larvae ml )1 instead of 10 ml )1 affects growth and survival of scallops (Gruffydd and Beaumont 1972;Ibarra et al 1997), but the response might differ between populations (Ibarra et al 1997). Torkildsen and Magnesen (2004) also suggest that larval density influences survival of P. maximus larvae, but they did not investigate this factor further.…”
Section: Discussionmentioning
confidence: 74%
“…Size and other physical cell characteristics (presence of umbonate larva, eyespot, double ring and foot) of S. limbatus larvae obtained in this study closely agree with those reported for S. tenebrosus (Parnell, 2002) and other Pectinoidea larvae, such as Argopecten ventricosus (Ibarra et al, 1997), Amusium balloti (Rose et al, 1988), Chlamys asperrimus (Rose and Dix, 1984), Nodipecten nodosus (De la Roche et al, 2002;Velasco et al, 2007) and Argopecten nucleus (Velasco et al, 2007). Nevertheless, our results diverge partially from those of Soria et al (2010), which reported longer sizes for pediveligers (234.0 ± 28.03 μm) than those obtained in the present study (185.2 ± 3.9 μm) for the same species.…”
Section: Embryonic and Larval Developmentsupporting
confidence: 91%
“…The optimum rearing density of planktotrophic larvae is crucial as over‐crowding may limit both swimming space and access to food resources and can lead to low dissolved oxygen and high nitrogenous waste concentrations – all of which may lead to reduced overall development and survival rates (Wang & Widdows ; Tomasso ; Ibarra, Ramirez & Garcia ; Doroudi & Southgate ). In scientific studies, echinoid larvae are typically reared at a density of ≤2 ind mL −1 (see review by Azad et al .…”
Section: Introductionmentioning
confidence: 99%